Application Of The Co-Creation Concept Of Written Batik Design For Fashion Design In The Teenage And Current Market Segment - Rahayu RAHAYU; Sudarmiatin SUDARMIATIN; Agus HERMAWAN (Indonesia Strategic Sustainability, 2022)
Entering the era of globalization, business development in any field has challenges, with so many varied Batik market segments, it is necessary to develop a more appropriate design by involving consumers to provide ideas or, more precisely, holding a co-creation of batik motifs by involving consumers from several market segments. Through the use of the co-creation concept, the purpose of this research is to transform a written batik product design based on local knowledge into a fashion design for the youth and contemporary market segment. This concept is a concept that gives consumers the freedom of ideas to create designs or revise existing designs according to the wishes of consumers. However, within limits provided by the Kudubanjar Batik Center as a producer, so with innovation and creation, new values will emerge in the design. Fashion for the teen and contemporary market segments because currently consumers tend to be able to play a role in the desired fashion design process. The method used for this design is to conduct FGD research to explore alternative fashion design creations. From the results of the FGD, a design sketch is prepared, which is then used as a guide for co-creation. Besides that, consumers are also free to design according to their wishes and current design trends. Based on the results of the research that has been done, there are eight fashion designs with the creation and innovation of batik motif designs designed based on local wisdom.